Bioacumulação de mercúrio e ecologia trófica em elasmobrânquios desembarcados na costa do Ceará, Brasil - Campos, Andréia dos Santos (2024)
Elasmobranchs are particularly vulnerable to mercury (Hg) contamination due to their biological characteristics, which include slow growth, late sexual maturity, low fecundity, and longevity. These traits facilitate the bioaccumulation of mercury in their tissues and organs. Additionally, Hg is highly toxic and can biomagnify throughout the trophic chain, posing a risk to the health of these fish and the humans who consume them. This study aims to determine the concentrations of total Hg in the muscle, liver and brain of elasmobranchs captured by artisanal fishing off the coast of Ceará, Brazil, aiming to understand aspects related to their biological and ecological factors, and the potential risks to animal and health human population that consumes this fish. 65 individuals of nine species of sharks and four species of rays, captured by artisanal fishing in the Mucuripe, Fortaleza/CE, were analyzed. For the detection of Hg and stable isotopes, the samples underwent acid digestion and were freeze-dried. Hg quantification was performed using a Cold Vapor Atomic Absorption Spectrophotometer (CV-AAS) and stable isotope analysis of δ13C and δ15N using a Continuous Flow Isotope Ratio Mass Spectrometer (Delta V Advantage, Thermo Scientific, Germany). In the study, Hg concentrations were significantly higher in muscle than in liver and brain, suggesting muscle as the main storage tissue for the metal. Two species of sharks, Carcharhinus limbatus and Ginglymostoma cirratum, demonstrated a significant correlation between Hg concentrations in muscle and brain, and between Hg in muscle and the total length of individuals, indicating bioaccumulation of the metal in this tissue. These relationships were not observed for any of the other species studied, probably due to the uniform size of the individuals and/or small sample number. The Hg concentrations of around 69% of the studied species exceeded the deleterious effect limit established for bony fish (LOAEL, 500 ng.g-1). Additionally, Hg was detected in the muscle and liver of Carcharhinus sp. and Rhizoprionodon porosus, indicating preliminary maternal transfer of the metal. Results like this demonstrate an important warning about the possible interference of Hg in the health of elasmobranchs. Sharks had significantly higher concentrations of Hg in their muscles than rays, a result that corroborates the ecological aspects of these fish, which indicate that sharks are organisms at the top of the food chain, while rays are mesopredators. Significant differences in the isotopic values of δ 13C and δ 15N between the studied elasmobranch species indicated variations in trophic ecology, corroborating the differences in foraging habitat and food preference between them. Moreover, isotopic niche analysis allowed identifying niche overlap between the species G. cirratum and Hypanus berthalutzae, which consume similar resources, but at different rates, which can limit competition for resources and promote coexistence between species. However, there were no significant differences in Hg concentrations between species, possibly due to the great variability of the metal in individuals with different sizes. Only one individual of Carcharhinus sp. presented Hg concentrations higher than the human consumption limit established by ANVISA (1,000 ng.g-1), reaching 1,034 ng.g-1. However, the Hg concentrations of around 76% of the studied species exceed the human consumption limit established for Ceará (local FSL, 280 ng.g-1). The risk coefficients for human consumption used in the study suggest that the shark species C. limbatus, Heptranchias perlo, Mustelus canis and R. porosus, and the ray H. berthalutzae, should have their limited consumption (EDI > RfD and THQ > 1), which may vary depending on the consumer's body weight and frequency of consumption. These results are crucial to understand the impact of Hg contamination on the health of elasmobranchs, in addition to providing information on the trophic ecology of these species and the risk of human consumption of this fish, especially considering that Brazil is one of the largest consumers of elasmobranchs in the world. world.